Linkages between psychosomatic disorders and generic subjetivation. Metasynthesis study - Claudia Larroca (Perspectivas Metodológicas​)
The objective of this Metasynthesis study is to provide scientific evidence by combining knowledge, based on the selection of previous studies that collect results about the processes of gender subjectivation and their link with the genesis of psychosomatic processes. From the methodological point of view, this study is carried out using the PRISMA method. Articles that address the subject are analysed, offering a detailed summary, of which the complete article will be used as the Unit of Analysis. Due to the current state of knowledge on the subject, it is considered pertinent to include in the sample articles related to the research object that, although they do not specifically address the research problem, offer theoretical arguments and data on the subject. Articles in Spanish will be selected. On the other hand, articles to which it is not possible to access the full content free are not included. Results: have been searched. 8 AU were selected, coming from the Google Scholar and Redalyc databases. The results found indicate that the processes of construction of ideals in the constitution of the feminine and masculine subjectivities are inscribed in the subjects (through culture, language and a complex web of meanings), these are so subtle that they reach make it difficult to oppose or even challenge it. This means that it is only possible to express this discomfort through somatic vulnerability. Traits of over adaptation towards generic ideals are observed, a mechanism highly associated with the genesis of psychosomatic disorders. It is concluded that the subject is constituted in the link, and in the exchange traces are inscribed, both in his body and in his process of subjectivation. The body is not exclusively determined by biology or culture. This interaction occurs within a cultural and symbolic context, where the ways of raising and existing social representations in the culture are building particular styles of gender subjectivity. Mechanisms that promote modes of connection with one's own body and particular ways of becoming ill are inscribed in this process of subjectivation.